The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1007/s10047-003-0226-8
|View full text |Cite
|
Sign up to set email alerts
|

Pannus formation in aortic valve prostheses in the late postoperative period

Abstract: We present three patients who underwent repeat aortic valve replacement for prosthetic valve dysfunction caused by tissue ingrowth in the late postoperative period. These patients (three women aged 48-51 years, mean 49.3 +/- 1.53 years) underwent operations for restriction of prosthetic valve leaflet movement by pannus in the left ventricular outflow tract. The interval from the previous operation ranged from 8.0 to 9.6 years (mean 9.6 +/- 2.0 years). The symptoms of the patients were New York Heart Associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…This finding may suggest that pannus formation does not cause any abnormality on TTE when it presents in minimal to mild degrees, but when it progresses to moderate to severe degrees, it can cause LVOT obstruction, and subsequently lead to PG elevation or LOM. These results were consistent with those of previous studies [19,20], which suggested that the hemodynamic effect of pannus formation depends on the extent and site of fibrous tissue. Pannus arising from the neointima in the periannulus of the left ventricular septum [21], may extend to the orifice and hinges of the prosthetic valve which results in restriction of either or both leaflets leading to severe narrowing of the inflow orifice, or severe stenosis may occur due to the narrowing of the LVOT by a circumferential pannus without restricting leaflet motion [19,20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding may suggest that pannus formation does not cause any abnormality on TTE when it presents in minimal to mild degrees, but when it progresses to moderate to severe degrees, it can cause LVOT obstruction, and subsequently lead to PG elevation or LOM. These results were consistent with those of previous studies [19,20], which suggested that the hemodynamic effect of pannus formation depends on the extent and site of fibrous tissue. Pannus arising from the neointima in the periannulus of the left ventricular septum [21], may extend to the orifice and hinges of the prosthetic valve which results in restriction of either or both leaflets leading to severe narrowing of the inflow orifice, or severe stenosis may occur due to the narrowing of the LVOT by a circumferential pannus without restricting leaflet motion [19,20].…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with those of previous studies [19,20], which suggested that the hemodynamic effect of pannus formation depends on the extent and site of fibrous tissue. Pannus arising from the neointima in the periannulus of the left ventricular septum [21], may extend to the orifice and hinges of the prosthetic valve which results in restriction of either or both leaflets leading to severe narrowing of the inflow orifice, or severe stenosis may occur due to the narrowing of the LVOT by a circumferential pannus without restricting leaflet motion [19,20]. In our study, the pannus was most frequently located at zone 1, which indicated the septal side of left ventricle, and the circumferential location was the second most common site.…”
Section: Discussionsupporting
confidence: 93%
“…Other authors indicate degeneration of a bioprosthesis as the most frequent cause of redo surgery as well [7, 17]. Each patient whose survival time is long enough needs redo surgery and this is connected with the limited durability of a bioprosthesis [18]. Taking that into account, it is proposed that implantation of bioprostheses be limited to patients over the age of 65.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting intima hypertrophy and degeneration in the valve might be important to sustain valvular flexibility and function [18,25]. Metabolites from the blood contact the surface of heart valvular tissue through direct diffusion [28].…”
Section: Discussionmentioning
confidence: 99%